#### Answer

$x=-5$

#### Work Step by Step

$3(x-4)-4(x-3)=x+3-(x-2)$
$3x-12-4x+12=x+3-x+2$
$-x=5$
$x=-5$

Published by
Pearson

ISBN 10:
0-32178-228-3

ISBN 13:
978-0-32178-228-1

$x=-5$

$3(x-4)-4(x-3)=x+3-(x-2)$
$3x-12-4x+12=x+3-x+2$
$-x=5$
$x=-5$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.